Трудовий договір в умовах спрощеного режиму регулювання трудових відносин - Косінцев, К. В.; Kosintsev, K. V. (Вісник Кримінологічної Асоціації України. - 2024. - № 1 (31). - С. 703-711, 2024)
З’ясовано сутність трудового договору в умовах спрощеного режиму регулювання трудових відносин. Розглянуто поняття «трудовий договір», розкрито положення норм чинного законодавства, яке регулює порядок укладення трудового договору в умовах спрощеного режиму регулювання трудових відносин. Доведено, трудовий договір в умовах спрощеного режиму регулювання трудових відносин - це особливий письмовий юридичний акт – угода між працівником і роботодавцем за якою працівник зобов’язується виконувати роботу, визначену цією угодою, а роботодавець – виплачувати працівникові заробітну плату і забезпечувати умови праці, необхідні для виконання роботи.

It is emphasized that the employment contract differs significantly from the category of contract in the general theoretical sense, which is connected with its following features: firstly, the employment contract provides for an agreement on the performance of professional, paid, labor activities carried out systematically at an enterprise, institution or organizations; secondly, in all cases, the parties to the employment contract are unchanged - the employee and the employer, who enter into labor relations through the conclusion of the agreement and determine the composition of mutual rights and obligations by the contract; thirdly, the employment contract is a written document, that is, it is a legal act that has an external expression and structure; it is concluded in accordance with the requirements of legal technique; fourthly, it is logical to consider an employment contract as "limitedly free", because a significant part of its content, form, mandatory conditions, features of use within the framework of individual employment relationships, terms, guarantees of conclusion are directly defined by the Labor Code and may be supplemented, but not violated ; fifthly, the direct and clear regulation has a procedure for concluding, terminating and terminating an employment contract, which takes place on the grounds specified by the Labor Code. It has been proven that an employment contract in the conditions of a simplified regime of regulation of labor relations is a special written legal act - an agreement between an employee and an employer under which the employee undertakes to perform the work specified in this agreement, and the employer undertakes to pay the employee a salary and provide working conditions necessary for performance of work.

Выяснена сущность трудового договора в условиях упрощенного режима регулирования трудовых отношений. Рассмотрено понятие «трудовой договор», раскрыто положение норм действующего законодательства, регулирующего порядок заключения трудового договора в условиях упрощенного режима регулирования трудовых отношений. Доказано, что трудовой договор в условиях упрощенного режима регулирования трудовых отношений – это особый письменный юридический акт – соглашение между работником и работодателем, по которому работник обязуется выполнять работу, определенную этим соглашением, а работодатель – выплачивать работнику заработную плату и обеспечивать условия труда, необходимые для исполнения работы.
Employment contract under the simplified labor regulation regime
Keywords: трудовий договір; спрощений режим регулювання; трудові правовідносини; працівник; роботодавець; employment contract; simplified regulatory regime; labor relations; employee; employer; трудовой договор; упрощенный режим регулирования; трудовые правоотношения; работник; работодатель